From fragmented to integrated healthcare managing hypertension post-stroke: a qualitative study - Azhari, Hala F.; Hewitt, Jonathan; O'Neill, Martin; Smith, Alexander; Quinn, Terence; Dawson, Jesse (Frontiers in Stroke, 2025)
IntroductionAs stroke incidence rises with an aging population, hypertension remains a critical modifiable risk factor for both primary and secondary stroke prevention. Effective management of hypertension post-stroke requires a shift from fragmented care to integrated, patient-centered approaches. This study explores the perspectives of stroke survivors and healthcare professionals on hypertension management and evaluates the acceptability of innovative strategies, including 24-h ambulatory blood pressure monitoring (ABPM).MethodsA qualitative study using grounded theory methodology was conducted through focus group interviews with stroke survivors and healthcare professionals in Wales and Scotland between January 2019 and December 2022. Participants included 48 individuals representing diverse backgrounds and experiences. Data were analyzed thematically to identify barriers and facilitators in hypertension management post-stroke.ResultsKey findings identified four major themes: the need for improved cooperation among multidisciplinary teams, knowledge gaps in stroke survivors regarding hypertension's role in stroke risk, the complexities of polypharmacy, and the potential benefits of ABPM for individualized care. Stroke survivors expressed a reliance on clinicians for hypertension management, while healthcare professionals emphasized the importance of empowering patients through education and self-management. ABPM emerged as a promising tool to enhance hypertension monitoring and support patient engagement, though practical challenges remain.DiscussionThe study underscores the importance of integrating patient education, multidisciplinary care, and advanced monitoring techniques like ABPM into hypertension management. Strengthening communication pathways between patients and healthcare providers can foster greater patient engagement and accountability. Addressing socio-economic barriers, improving patient-clinician communication, and implementing holistic care strategies are critical for reducing recurrent stroke risk. These findings emphasize the need for systemic reforms and targeted interventions to bridge gaps in hypertension care delivery post-stroke.